Idiopathic Toe-Walking in Children and Adolescents: Diagnosis, Natural History, and Treatment Options. Issue 2 (February 2022) - Freiman, Halle D.; Mensah, Curtis; Codrington, Jason; Frick, Steven L.
Abstract : Idiopathic toe-walking is a diagnosis of exclusion. The natural history of idiopathic toe-walking has not been studied in many children; we identified only 1 prospective study. Of children without equinus contractures who were toe-walking before the age of 5.5 years, 59% had spontaneous resolution of toe-walking by 5.5 years of age, and 79%, by the age of 10 years. Adverse consequences of toe-walking into adulthood have not been reported, but may exist, and further research is needed to define and clarify. If parents desire treatment to resolve their child's toe-walking, surgical lengthening of the Achilles tendon is the treatment with the highest chance of success and lowest relapse rate, and thus far, no complications have been reported in any surgical series.